Extensive severe fever with thrombocytopenia syndrome virus contamination in surrounding environment in patient rooms. (August 2018) - Ryu, B.-H.; Kim, J.Y.; Kim, T.; Kim, M.-C.; Kim, M.J.; Chong, Y.-P.; Lee, S.-O.; Choi, S.-H.; Kim, Y.S.; Woo, J.H.; Kim, S.-H.
Abstract: Objectives: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne disease in Korea and China. Although there is previous evidence of person-to-person transmission via direct contact with body fluids, the role of environmental contamination by SFTS virus (SFTSV) in healthcare settings has not been established. We therefore investigated the contamination of the healthcare environment by SFTSV. Methods: We investigated the possible contamination of hospital air and surfaces with SFTSV transmission by collecting air and swabbing environmental surface samples in two hospitals treating six SFTS patients between March and September 2017. The samples were tested using real-time RT-PCR for SFTS M and S segments. Results: Of the six SFTS patients, four received mechanical ventilation and three died. Five rooms were occupied by those using mechanical ventilation or total plasma exchange therapy in isolation rooms without negative pressure and one room was occupied by a patient bedridden due to SFTS. SFTSV was detected in 14 (21%) of 67 swab samples. Five of 24 swab samples were obtained from fomites including stethoscopes, and 9 of 43 were obtained from fixed structures including doorknobs and bed guardrails. Some samples from fixed structures such as television monitors and sink tables were obtained in areas remote from the patients. SFTSV RNA was not detected in five air samples from three patients' rooms. Conclusions: Our data suggest that SFTSV contamination was extensive in surrounding environments in SFTS patients' rooms. Therefore, more strict isolation methods and disinfecting procedures should be considered when managing SFTS patients.